Litter and Root Manipulations Provide Insights into Soil Organic Matter Dynamics and Stability. Issue Volume 78:Issue Supplement 1(2014) (14th July 2014) - Lajtha, Kate; Bowden, Richard D.; Nadelhoffer, Knute
Abstract : Understanding controls on C stored in soil organic matter (SOM) is of critical importance to models of biospheric C sequestration. Although ecosystem C models assume a strong relationship between plant litter inputs and soil C accumulation, there is little experimental evidence to support this assumption. The Detritus Input and Removal Treatments (DIRT) experiment at Harvard Forest was designed to assess how rates and sources of plant litter inputs control the accumulation and dynamics of organic matter in soils across decadal time scales. Carbon and SOM quantity and quality were measured in O horizon and mineral soil in five treatments: control, double litter, no litter, no roots, and no inputs. After 20 yr of manipulation, doubling litter inputs did not increase bulk soil C or N content, light or heavy fraction pools of C, or measures of labile C. However, the activities of two key enzymes (β‐glucosidase and phosphomonoesterase) increased 30% with litter additions. Exclusion of either aboveground litter or root inputs resulted in sharp declines in O‐horizon C and N but smaller decreases in total mineral soil C and N. However, decreases in light fraction C and soil respiration were significant in removal treatments. Litter exclusion resulted in an 18% decline in total profile mineral soil C, whereas root exclusion resulted in a 9% decline, indicating the importance of aboveground inputs to long‐term C pools. Soil C pools in this forest do not respond linearly or immediately to aboveground or belowground litter inputs, and thus efforts to sequester C by managing productivity and associated litter inputs will probably not result in increased C storage in short time frames.